Экранирование однородного переменного магнитного поля электропроводящим кольцом - Гринченко, В.С.; Чунихин, К.В. (Електротехніка і електромеханіка, 2015)
Путем аналитического и численного моделирования исследована эффективность экранирования однородного гармонического магнитного поля при помощи электропроводящего кольца. Установлены зависимости коэффициента экранирования от радиуса кольца и его поперечного сечения. Определены параметры электропроводящего кольца, применение которого позволяет снизить действующее значение магнитной индукции на 30 %. Шляхом аналітичного та чисельного моделювання досліджено ефективність екранування однорідного гармонійного
магнітного поля за допомогою електропровідного кільця. Встановлено залежності коефіцієнту екранування від радіуса кільця та його поперечного перерізу. Визначено параметри електропровідного кільця, застосування якого дозволяє
знизити діюче значення магнітної індукції на 30 %. The magnetic and electromagnetic shields are used to reduce
the magnetic field in local spaces. Usually these shields are
implemented in the form of a box or a cylinder. At the same time
the magnetic field reduction in local spaces by means of passive
loops is not considered in detail yet. So, the present study considers shielding capabilities of a circular passive loop. The authors have performed an analytical and numerical modeling of a
process of a uniform harmonic magnetic field shielding. The
simulated results permit to find out the spatial distribution of the
shielded magnetic field. Dependencies of shielding effectiveness
on the passive loop radius and cross-section are determined.
Moreover, the non-monotonic behavior of the loop radius dependence is shown. We have substantiated that the shielded
volume of a circular passive loop is advisable to limit by the
sphere with a half loop radius. Presented results give parameters of the circular passive loop that reduces the rms value of
the magnetic flux density by 30 %.